2013
DOI: 10.1111/1471-0528.12363
|View full text |Cite
|
Sign up to set email alerts
|

Third‐ and fourth‐degree perineal tears among primiparous women in England between 2000 and 2012: time trends and risk factors

Abstract: Objective To describe the trends of severe perineal tears in England and to investigate to what extent the changes in related risk factors could explain the observed trends.Design A retrospective cohort study of singleton deliveries from a national administrative database.Setting The English National Health Service between 1 April 2000 and 31 March 2012.Population A cohort of 1 035 253 primiparous women who had a singleton, term, cephalic, vaginal birth.Methods Multivariable logistic regression was used to est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

29
278
4
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 345 publications
(314 citation statements)
references
References 72 publications
29
278
4
3
Order By: Relevance
“…The number needed to treat to prevent one obstetric anal sphincter injury during vacuum‐assisted delivery was found to be 50. This finding is supported by previous studies, which reported a decrease in obstetric anal sphincter injuries when episiotomy was used in operative vaginal deliveries 8, 25, 28, 29. Jangö et al report a number needed to treat of 23 mediolateral episiotomies and Raisänen et al report a number needed to treat of 66 lateral episiotomies to prevent one case of obstetric anal sphincter injury in vacuum‐assisted deliveries, thus favoring more frequent use of episiotomy in such cases 28, 30.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The number needed to treat to prevent one obstetric anal sphincter injury during vacuum‐assisted delivery was found to be 50. This finding is supported by previous studies, which reported a decrease in obstetric anal sphincter injuries when episiotomy was used in operative vaginal deliveries 8, 25, 28, 29. Jangö et al report a number needed to treat of 23 mediolateral episiotomies and Raisänen et al report a number needed to treat of 66 lateral episiotomies to prevent one case of obstetric anal sphincter injury in vacuum‐assisted deliveries, thus favoring more frequent use of episiotomy in such cases 28, 30.…”
Section: Discussionsupporting
confidence: 90%
“…As supported by the literature, we found operative vaginal delivery7, 8, 13, 14, 15 to be an independent risk factor for sphincter damage. In particular, forceps delivery has consistently been shown to represent one of the major risk factors for obstetric anal sphincter injuries 16, 17, 18, 19.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations